Human rights and corruption. From convergence to implementation - Nash Rojas, Claudio (2025)
In recent years, there has been solid progress in the process of convergence between the international protection of human rights and the fight against corruption. One of the main challenges of this process is to find effective mechanisms for advancing in the interaction between the two agendas. To address this challenge, this article specifically asks: how can the phenomenon of corruption be incorporated into the international protection of human rights? To answer this question, we analyze the various procedures available to international human rights organizations to establish how it is possible to incorporate the phenomenon of corruption into international oversight. The central proposition is that through a strategic approach, the main obstacles that hinder the full realization of the potential of the convergence process between the two thematic agendas can be resolved. In the article, we will develop these obstacles and how to conduct this strategic approach. Our hypothesis is that a correct interpretation of the phenomenon of corruption and its impact on human rights allows for more effective and comprehensive international oversight.